Antimicrobial activity of ozonated oils and their applications in medicine – a narrative review - Pyatkovskyy, Taras; Pokryshko, Olena (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Ozonated oils have emerged as promising agents due to their potent antimicrobial properties and broad therapeutic potential across various medical fields. This review aims to evaluate the antibacterial activity of ozonated oils, focusing on their applications in dermatology, dentistry, ophthalmology, gynecology, and proctology, while addressing their safety profiles and limitations. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This review compiles and evaluates peer-reviewed publications on the antibacterial properties and therapeutic uses of ozonated oils. The authors conducted a comprehensive literature review by searching through the largest scientific databases using Google Scholar, Google Patents, Scopus, Web of Science, and PubMed within the last 15 years. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. Ozonated oils exhibited strong antibacterial effects against a wide range of microorganisms, including those resistant to antibiotics. Their efficacy has been confirmed in treating conditions such as onychomycosis, oral and vaginal candidiasis, and MRSA skin infections, among others. Clinical studies highlight their ability to reduce symptoms and improve outcomes in ophthalmic applications as well. Despite their effectiveness there are limitations which include a lack of long-term safety data, insufficient number of studies conducted on human subjects. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Ozonated oils have a lot of potential as antimicrobials that can be used in a variety of medicinal fields. However, further clinical trials are needed to establish their long-term safety and efficacy.